The hepatoprotective potentials of Olea europaea L. leaves against carbon tetrachloride-induced hepatic injury in rats - Amber Ayaz Memon; Lubna Naz (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the therapeutic effects of Olea europaea L. leaves extract on carbon tetrachloride-induced liver injury in rats. Method: The experimental study was conducted at the Department of Physiology, University of Karachi, Karachi, in July 2021, and comprised Albino Wistar male rats weighing 180-220gm. The animals were divided into control group I, carbon tetrachloride group II, Olea europaea L. + carbon tetrachloride group III and Olea europaea L. group IV. In Vitro model of hepatic toxicity was developed by carbon tetrachloride. A daily dose of 50mg/kg of aqueous extract of olive leaves was administered orally and 0.8ml/kg of carbon tetrachloride was administered twice a week subcutaneously for 28 days. On the 29th day, the animals were sacrificed, and tested for hepatic enzymes, lipid peroxidation markers and histopathology. Data was analysed using SPSS 20. Results: Of the 24 rats, 6(25%) were in each of the 4 groups. Alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and total bilirubin levels were significantly reduced (p<0.05) in group II whereas, 4- hydroxynonenal, isoprostane and malondialdehyde levels were significantly increased (p<0.05). However, total antioxidant level increased significantly (p<0.05) in group III compared to group II. Histopathology showed severe liver damage in group II and mild damage in group III. Conclusion: Olea europaea L. leaves extract was found to have profound hepatoprotective effects. Key Words: Antioxidants, Olea, carbon tetrachloride, alanine transaminase, alkaline phosphatase, liver injury, chronic, lipid peroxidation, bilirubin, aspartate aminotransferases, malondialdehyde, isoprostanes